Table of contents, editorial board, and other front matter - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1979)
Editorial front matter and table of contents for vol.61, no.4, Dec.-Jan (1979) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education